2012
DOI: 10.1103/physrevlett.109.085303
|View full text |Cite
|
Sign up to set email alerts
|

Exotic Quantum Spin Models in Spin-Orbit-Coupled Mott Insulators

Abstract: We study cold atoms in an optical lattice with synthetic spin-orbit coupling in the Mott-insulator regime. We calculate the parameters of the corresponding tight-binding model using Peierls substitution and "localized Wannier states method" and derive the low-energy spin Hamiltonian for bosons and fermions. The spin Hamiltonian is a combination of Heisenberg model, quantum compass model and Dzyaloshinskii-Moriya interactions and it has a rich classical phase diagram with collinear, spiral and vortex phases. We… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
218
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(223 citation statements)
references
References 48 publications
(49 reference statements)
5
218
0
Order By: Relevance
“…(2) becomes classical. Some interesting results on the possible rich classical ground states at some sets of general (α, β) in the Heisenberg-Kitaev-DM representation were attempted numerically in [25,26]. Here, we plan to study the quantum phenomena in the RH model at generic (α, β).…”
Section: Classification By Wilson Loops and An Exactly Solvable mentioning
confidence: 99%
“…(2) becomes classical. Some interesting results on the possible rich classical ground states at some sets of general (α, β) in the Heisenberg-Kitaev-DM representation were attempted numerically in [25,26]. Here, we plan to study the quantum phenomena in the RH model at generic (α, β).…”
Section: Classification By Wilson Loops and An Exactly Solvable mentioning
confidence: 99%
“…In particular, in the strongly interacting regime, a super-exchange spin model with Dzyaloshinskii-Moriya (DM) type interactions [17,18] can be derived by second-order perturbation theory. And various exotic spin-textures are predicted by classical Monte-Carlo simulations or spin-wave analysis of the effective spin model [12][13][14][15]. Similar spin textures induced by the DM-type interactions have also been found in various solid state materials and attracted great interest [19][20][21].…”
Section: Introductionmentioning
confidence: 99%
“…This has motivated experimental developments in the field of quantum simulation with ultracold atoms, where tunable SO coupling and more generally synthetic non-abelian gauge fields are created in both neutral bosonic atoms [5][6][7] and fermionic atoms [8,9] via Raman processes or by driven optical lattices [10]. This progress has stimulated interesting studies on the physics of SO coupled Bose-Bose mixtures subjected to an optical lattice [11][12][13][14][15][16], where the Mott insulator to superfluid phase transition [11,12], magnetic order in the deep Mott insulator regime [12][13][14][15], and superfluid phases [11,12,14,16] are investigated. In particular, in the strongly interacting regime, a super-exchange spin model with Dzyaloshinskii-Moriya (DM) type interactions [17,18] can be derived by second-order perturbation theory.…”
Section: Introductionmentioning
confidence: 99%
“…The realisation of the deep XY-regime with this particular driving protocol is limited, since |J 2 (4ζ Φ )| < 1 but, at finite S z S z -interaction a semi-classical study showed that vortices persist and can be thought of as half-skyrmion configurations of the Neél field [48][49][50]. Another interesting feature of the spin Hamiltonian is that it exhibits a Dzyaloshinskii-Moriya (DM) interaction term [51][52][53][54], D mn · (S m+1,n × S mn ). The DM coupling is spatially-dependent, polarised along the z-direction D mn = sin(φ mn )J 2 (4ζ Φ )n z /2, and present only along the x-lattice direction.…”
mentioning
confidence: 99%